2004
DOI: 10.1523/jneurosci.1586-03.2004
|View full text |Cite
|
Sign up to set email alerts
|

The Glutamate Transporter GLT1a Is Expressed in Excitatory Axon Terminals of Mature Hippocampal Neurons

Abstract: GLT1 is the major glutamate transporter of the brain and has been thought to be expressed exclusively in astrocytes. Although excitatory axon terminals take up glutamate, the transporter responsible has not been identified. GLT1 is expressed in at least two forms varying in the C termini, GLT1a and GLT1b. GLT1 mRNA has been demonstrated in neurons, without associated protein. Recently, evidence has been presented, using specific C terminus-directed antibodies, that GLT1b protein is expressed in neurons in vivo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

20
251
2
1

Year Published

2004
2004
2013
2013

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 248 publications
(274 citation statements)
references
References 74 publications
20
251
2
1
Order By: Relevance
“…In the present and in previous studies (Minelli et al, 2001;Melone et al, 2001), we observed GLT-1 ir exclusively in astrocytic processes, in line with the results of most reports (Danbolt, 2001). Recently, Chen et al (2004), using the same antibody used here, reported that in the hippocampus of animals perfused without glutaraldehyde only 65-70% of immunoreactivity was astrocytic, the remaining being neuronal. Even though these findings await confirmation in neocortical areas of humans, they raise the possibility that the changes reported here may not depend on altered astrocytic GLT-1 expression alone.…”
supporting
confidence: 93%
“…In the present and in previous studies (Minelli et al, 2001;Melone et al, 2001), we observed GLT-1 ir exclusively in astrocytic processes, in line with the results of most reports (Danbolt, 2001). Recently, Chen et al (2004), using the same antibody used here, reported that in the hippocampus of animals perfused without glutaraldehyde only 65-70% of immunoreactivity was astrocytic, the remaining being neuronal. Even though these findings await confirmation in neocortical areas of humans, they raise the possibility that the changes reported here may not depend on altered astrocytic GLT-1 expression alone.…”
supporting
confidence: 93%
“…and perfused transcardially with a flush (B1 min) of saline, followed by 4% paraformaldehyde in phosphate buffer (PB). The brains were removed, postfixed in the same fixative for 7 days (Chen et al, 2004), and cut on a Vibratome in 50-mm parasagittal sections, which were collected in PB in serial groups of 5 and then used for immunocytochemistry (Minelli et al, 2001;Chen et al, 2004;Melone et al, 2005). Sections were incubated in a solution containing a mixture of GLT-1 (1 : 1000; Millipore; AB1783; Bragina et al, 2006) and mGlurR-2/3 (1 : 50; Millipore; AB1553; Testa et al, 1998) primary antibodies.…”
Section: Immunocytochemistrymentioning
confidence: 99%
“…However, more recent studies have established that GLT1 is far more abundant than GLT1b in both neurons and astrocytes, indicating that GLT1b is neither unique to neurons, nor is it the predominant isoform in neurons. 54,55 In retrospect, it is possible that the use of various immunohistochemical techniques, such as employing ultrathin sections and fixation without glutaraldehyde, may have produced the confusing results observed in 2002.…”
Section: Localization Of Glt1mentioning
confidence: 99%